IMPROVING STUDENTS’ LEARNING OUTCOMES IN BIOLOGY THROUGH THE CONTEXTUAL TEACHING AND LEARNING MODEL BY YEAR VII-A STUDENTS OF MTsN 1 WEST ACEH - Nurmailis Nurmailis (Pedagogi: Jurnal Ilmiah Pendidikan, 2021)
This study aims to determine "The Improvement of Students’ Learning Outcomes in Biology through Contextual Teaching and Learning Models by Year VII-A Students of MTsN 1 West Aceh". The research sample was Year VII-A students, with the total number of students was 25 students. This study used Classroom Action Research (CAR) with the methods of observation, data collection, tests, documentation and data analysis. This study used two cycles to determine the improvement of Biology learning outcomes in class VII-A MTsN 1 West Aceh. The results of this study indicated that the Contextual Teaching And Learning model can improve the learning outcomes of Year VII-A students of MTsN 1 West Aceh. As for the results, it can be seen from the learning outcomes in the pre-cycle, the first and the second cycles. The students’ learning outcomes in the pre-cycle was only 8 students (32%) reached the passing grades. In the first cycle, students’ learning outcomes increased to 17 students (68%) who reached the passing grades and in the second cycle, there were 25 students (100%) completed.